Confined interfacial alloying of multilayered Pd-Ni nanocatalyst for widening hydrogen detection capacity - Lee, Young Ahn; Duy, Le Thai; Han, Seungik; An, Hyesung; Park, Jucheol; Singh, Ranveer; Kim, Hyun You; Seo, Hyungtak (Sensors and Actuators, B: Chemical, 2021)
Nanostructuring of catalysts, such as Pd, is of interest for exploiting their unique surface properties cost-effectively for various applications, especially high-dose hydrogen sensing and storage. Although various Pd modifications have been reported, they have a drawback of structural instability in applications involving high hydrogen doses. Thus, our development of a multilayered Pd-Ni nanocatalyst (PN, three Pd and two Ni layers) is proposed. Here we show the confined self-alloying of Pd and Ni at their interfaces, forming ultrathin 2D-like PdNix layers that facilitate ultrafast hydrogen detection over a wide range (20 ppm to 100 %, workable at 25–100°C) with extraordinary reversibility (> 30,000 cycles, tested at 100°C). That phenomenon of our 11-nm-thick nanocatalyst is justified through experimental measurements and simulation. Thereby, the obtained results revealed the high potency of our PN with the confined self-alloying for high-dose and wide-range hydrogen sensing applications and showed a new way to construct better catalytic nanosystems at low cost.
Keywords: High potency; Hydrogen detection; Hydrogen-sensing; Interfacial alloying; Multi-layered; Nano-catalyst; Nano-structuring; Structural instability; Confined alloying; Hydrogen sensing; Multilayering; Nanocatalyst; Pd-Ni